Sosialisasi Penggunaan Aplikasi Satu Sehat untuk Mengetahui Indeks Massa Tubuh Remaja di SMA Modern Al-Rifa’e Gondang Legi Malang - Ali, Amir (STIKES Yayasan RS.Dr.Soetomo, 2025)
Adolescence begins at the age of 10-18 years, and there are three stages of adolescent development. At each stage, adolescents will experience many changes, both physically, cognitively, and emotionally. During adolescence, habits and behaviors begin to form, one of which is eating habits. Good eating habits for adolescents can help achieve maximum growth and thus be beneficial for maintaining their health. Eating behavior in terms of eating habits shown by adolescents includes consuming snacks and fast food. This will affect nutritional problems. Nutritional problems occur not only from deficiencies but also from an imbalance in excessive food consumption, which can lead to overnutrition (obesity). Therefore, it is necessary to understand the importance of knowing the nutritional status of adolescents. The method uses BMI (body mass index) measurements. BMI measurements use the SATU SEHAT application from the Ministry of Health on each mobile phone of students at Al-Rifa'E Modern High School, Gondang Legi, Malang. This community service activity involved 30 female students. This activity resulted in skills in using the SATU SEHAT application installed on each mobile phone of students at Al-Rifa'E Modern High School, Gondang Legi, Malang. Where students of Al-Rifa'E Gondang Legi Malang Modern High School can understand the use and benefits of the SATU SEHAT application for BMI measurement so that they can achieve their ideal body size that they are not susceptible to disease.